The image of birds in Czech literature - Anikina, Tatiana; Stackelberg, Natalia (Bohemistyka, 2019)
This article is devoted to show the common grounds of Czech and other European literature. Images of birds have an imposing tradition of use in Czech literature. They are characterized by a variety of meanings and history of existence. There are both traditional and everyday folklore images, such as mythologeme of raven for the first one, and geese for the second, which have different semantic workloads. Discussion of the image of birds in the Czech literature is the basement of conclusions about the common ground that brings Czech and European literature together. Moreover, it also gives us more details about Czech national identity, the specifics of its literary schools and movements and the originality of the author’s vision of the world.